Food security status and cardiometabolic health by sex/gender and race/ethnicity among adults in the United States - Jamie A. Murkey; Symielle A. Gaston; Dana M. Alhasan; Christopher W. Payne; W. Braxton Jackson; Chandra L. Jackson (BMC, 2024)
Abstract Background Minoritized racial/ethnic groups and women in the United States (US) are disproportionately burdened by food insecurity, which likely contributes to disparities in cardiovascular health (CVH). Disparities are projected to widen due to the worsening climate crisis that is straining the agricultural system including food supplies. Nonetheless, studies have not investigated the relationship between food security status and 'ideal' CVH in a large, nationally-representative and racially/ethnically diverse US sample. Methods and results We investigated household food security status in relation to 'ideal' CVH among US adults (N = 157,001) using 2014-2018/2020 National Health Interview Survey data. Food security status was defined as very low, low, marginal, or high. A summed score of 4 health behaviors and 3 clinical factors totaling 7 different measures was dichotomized (yes/no) to assess modified 'ideal' CVH (mICVH). Using Poisson regression with robust variance, we estimated prevalence ratios (PRs) and 95% CIs of mICVH by household food security status. We stratified models by sex/gender and race/ethnicity. Very low food security prevalence was higher among non-Hispanic (NH)-Black (8.0%) compared to Hispanic/Latinx (5.1%), NH-White (3.1%) and NH-Asian (1.7%) adults. The association between very low versus high food security and mICVH was stronger among women (PR = 0.23 [95% CI: 0.17-0.31]) than men (PR = 0.48 [95% CI: 0.35-0.66]). Compared to NH-White adults with high food security, racially/ethnically minoritized groups with very low to high food security were generally less likely (range: [PRvery low = 0.25[95% CI: 0.14-0.44] - [PRhigh = 0.88 [95% CI: 0.79-0.97]) to meet mICVH criteria. Conclusions Food insecurity was associated with lower mICVH prevalence and racially/ethnically minoritized groups were disproportionately burdened.